PENERAPAN MODEL PEMBELAJARAN INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SEJARAH SISWA KELAS VIII I SMPN 27 PEKANBARU - Jumiati '; Bedriati Ibrahim; Asril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: Application of learning models Index Card Match constitute model learning that make student more aktive in learning, learning model in this stir student that avtive answer the question written papper. Mach with answer is no in another paper. By applying learning models this can help liveliness to student more aktive that student easier understand or remember will matter they receive and help in crease mastery subject matter so that can improve result student learning. The purpose of this study is 1) to determine the application of the index card match the learning models can improve student learning in social science learning in class VIII I SMPN 27 Pekanbaru, 2) to know teacher activity with application learning index card match, 3) to know student activity in lesson the teacher. In this research use this type of research class action which research approach descriptive qualitative. The research was conducted in to cycles. Subject in this study is all students in class VIII I SMPN 27 Pekanbaru which number three of eight student. Data analysis tecnique apply descriptive qualitative analysis has observation and study result test and descriptive qualitative. The result of research show theacer activity durng two sycles increased at 19 with enought category abnd 22 with good category in cycle I, and 26 with good category and 32 with very good category in cycle II. Student activity increased by a score 623 white enough category and 677 whith enough category in cycle I, Score 892 whith good category and 1.104 whith very good category in cycle II. The while students learning result also increased for two sycles in sycle I with an average value 73,68 increased to 85,13 in cycle II. So can be conclude that through by using models index card match can increase teacher activity, student activity and student learning result sosial sciences of history student at class VIII I in SMPN 27 Pekanbaru.Key word : Index Card Match Models, Learning, Study Result